Clinical Characterization of Antiphospholipid Syndrome by Detection of IgG Antibodies Against β2‐Glycoprotein I Domain 1 and Domain 4/5: Ratio of Anti–Domain 1 to Anti–Domain 4/5 As a Useful New Biomarker for Antiphospholipid Syndrome. Issue 8 (28th July 2015) - Andreoli, Laura; Chighizola, Cecilia B.; Nalli, Cecilia; Gerosa, Maria; Borghi, M. Orietta; Pregnolato, Francesca; Grossi, Claudia; Zanola, Alessandra; Allegri, Flavio; Norman, Gary L.; Mahler, Michael; Meroni, Pier Luigi; et al.
<x xml:space="preserve">Abstract</x> Objective It has been suggested that only antibodies against domain 1 (D1) of β2‐glycoprotein I (β2GPI) are pathogenic and diagnostic. The role of antibodies against other β2GPI domains is still debated. This study was undertaken to evaluate the clinical relevance of domain specificity profiling of anti‐β2GPI IgG antibodies in antiphospholipid syndrome (APS) patients and in control groups of patients with systemic autoimmune rheumatic diseases and in asymptomatic antiphospholipid antibody (aPL) carriers. Methods We evaluated 159 subjects with persistently positive, medium or high‐titer anti‐β2GPI IgG, including 56 patients with thrombotic (obstetric or nonobstetric) primary APS, 31 women with obstetric primary APS, 42 aPL‐positive patients with systemic autoimmune rheumatic diseases, and 30 asymptomatic aPL carriers. One hundred healthy donors were included. Anti‐β2GPI D1 and D4/5 IgG were tested on research enzyme‐linked immunosorbent assays containing recombinant β2GPI domains. Results As compared to other groups, aPL carriers displayed higher frequency/titer of anti‐D4/5 IgG. Unlike anti‐D4/5, anti‐D1 IgG antibodies were more frequent and at higher titer in triple than in single or double aPL‐positive subjects. An anti‐D1 to anti‐D4/5 ratio of ≥1.5 was predictive of systemic autoimmunity (odds ratio 3.25 [95% confidence interval 1.45–7.49], P = 0.005). Neither anti‐D1 nor anti‐D4/5 antibodies were associated with APS clinical criteria. Conclusion Anti‐D1 IgG is the preferential specificity not only in vascular and obstetric primary APS, but also in patients with systemic autoimmune rheumatic disease with no clinical features of APS. Conversely, aPL carriers do not have a polarized profile toward D1. Combined testing for anti‐β2GPI IgG with different domain specificity allows a more accurate aPL profiling, with polarization toward anti‐D1 IgG as a possible fingerprint of systemic autoimmunity.